Organized sport trajectories from childhood to adolescence and health associations - Howie, Erin; McVeigh, Joanne; Smith, Anne; Straker, Leon (Lippincott Williams & Wilkins, 2016)
Introduction: The purpose of this study was to identify unique organized sport trajectories from early childhood to late adolescence in an Australian pregnancy cohort, the Raine Study. Methods: Participation in organized sport was assessed at ages 5, 8, 10, 14, and 17 yr. Physical activity, body composition, and self-rated physical and mental health were assessed at the age of 20 yr. Latent class analysis was used to identify patterns of sport participation. To assess the internal validity of the trajectory classes, differences in health characteristics between trajectories were analyzed using generalized linear models. Results: For girls, three trajectory classes were identified: consistent sport participators (47.5%), sport dropouts (34.3%), and sport nonparticipators (18.1%). For boys, three trajectory classes were identified: consistent sport participators (55.2%), sport dropouts (36.9%), and sport joiners (8.1%). For girls, there were overall differences across trajectory classes in lean body mass (P = 0.003), lean mass index (P = 0.06), and physical health (P = 0.004). For boys, there were differences across classes in physical activity (P = 0.018), percent body fat (P = 0.002), lean body mass (P < 0.001), lean mass index (P < 0.001), physical health (P = 0.06), and depression scores (P = 0.27).Conclusion: This study identified unique, sex-specific trajectories of organized sport participation. The differences in health outcomes between trajectory classes, such as participants with consistent sport participation having more preferable health outcomes at the age of 20 yr, support the internal validity of the trajectories. Strategies are needed to identify and encourage those in the dropout trajectory to maintain their participation and those in the nonparticipator or joiner trajectories to join sport earlier. Specifically, interventions to encourage early sport participation in girls and help nonparticipating boys to join sport during adolescence may help more children receive the benefits of sport participation.